An Analysis of Securities Investment in PT Bank Central Asia Tbk within the Indonesian Capital Market Context - Ravina Alya Lubis; Atika Farandina Rangkuti; Nadila Natasya; Henny Andriyani Wirananda; Shita Tiara (Jurnal EMT KITA, 2026)
This study aims to analyze the securities investment strategy carried out by PT Bank Central Asia Tbk (BCA) in the Indonesian capital market during the 2020–2024 period. The study uses a quantitative approach with secondary data obtained from the company's annual report and official sources of the Indonesia Stock Exchange. The results of the study show that BCA has consistently increased the value of its investment portfolio through asset diversification, including government bonds, sukuk, corporate bonds, reverse repos, and stocks classified as FVTPL assets. This investment strategy demonstrates BCA's ability to respond to market dynamics and utilize capital market instruments that have controlled risks and competitive returns. The significant increase in the value of the securities portfolio by 62.7% in five years proves the effectiveness of the company's investment expansion strategy. Amid global performance and domestic economic fluctuations, BCA has succeeded in maintaining financial performance and stability through adaptive risk management and selective utilization of investment opportunities. These findings indicate that securities investment is an important instrument in supporting financial resilience and company value in the capital market.